Salivary Therapeutic Drug Monitoring of Antimicrobial Therapy: Feasible or Futile? - Davies Forsman, Lina; Kim, Hannah Yejin; Nguyen, Thi Anh; Alffenaar, Jan-Willem C. (Clinical pharmacokinetics, 2024)
Personalised drug dosing through therapeutic drug monitoring (TDM) is important to maximise efficacy and to minimise toxicity. Hurdles preventing broad implementation of TDM in routine care include the need of sophisticated equipment and highly trained staff, high costs and lack of timely results. Salivary TDM is a non-invasive, patient-friendly alternative to blood sampling, which has the potential to overcome barriers with traditional TDM. A mobile UV spectrophotometer may provide a simple solution for analysing drug concentrations in saliva samples. Salivary TDM utilising point-of-care tests can support personalised dosing in various settings including low-resource as well as remote settings. In this opinion paper, we describe how hurdles of implementing traditional TDM may be mitigated by salivary TDM with new strategies for patient-friendly point-of-care testing.